Moisture and Salinity Stress Induced Changes in Biochemical Constituents and Water Relations of Different Grape Rootstock Cultivars - Satisha Jogaiah; Sahadeo D. Ramteke; Jagdev Sharma; Ajay Kumar Upadhyay (International Journal of Agronomy)
Ten grape rootstocks were subjected to moisture and salinity stress in two separate experiments. The influence of these stresses on gas exchange, water relation, and biochemical parameters was monitored at various stages of stress cycle. Both stresses indicated significant changes in the physiological and biochemical parameters studied. Some biochemical constituents increased by several folds in few rootstock cultivars which also recorded increased osmotic potential suggesting their role in osmotic adjustment. Some of the rootstock cultivars such as 110R, 1103P, 99R, Dogridge, and B2/56 recorded increased phenolic compounds under stressed conditions. The same rootstock also recorded increased water use efficiency. The increased accumulation of phenolic compounds in these cultivars may indicate the possible role of phenolic compounds as antioxidants for scavenging the reactive oxygen species generated during abiotic stresses thus maintaining normal physiological and biochemical process in leaves of resistant cultivars.